Association Between Lack of Blinding and Mortality Results in Critical Care Randomized Controlled Trials: A Meta-Epidemiological Study*. Issue 10 (30th April 2021) - Martin, Guillaume L.; Trioux, Théo; Gaudry, Stéphane; Tubach, Florence; Hajage, David; Dechartres, Agnès
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To investigate whether intervention effect estimates for mortality differ between blinded and nonblinded randomized controlled trials conducted in critical care. We used a meta-epidemiological approach, comparing effect estimates between blinded and nonblinded randomized controlled trials for the same research question. DATA SOURCES: Systematic reviews and meta-analyses of randomized controlled trials evaluating a therapeutic intervention on mortality in critical care, published between January 2009 and March 2019 in high impact factor general medical or critical care journals and by Cochrane. DATA EXTRACTION: For each randomized controlled trial included in eligible meta-analyses, we evaluated whether the trial was blinded (i.e., double-blinded and/or reporting adequate methods) or not (i.e., open-label, single-blinded, or unclear). We collected risk of bias evaluated by the review authors and extracted trial results. DATA SYNTHESIS: Within each meta-analysis, we compared intervention effect estimates between blinded and nonblinded randomized controlled trials by using a ratio of odds ratio (< 1 indicates larger estimates in nonblinded than blinded randomized controlled trials). We then combined ratio of odds ratios across meta-analyses to obtain the average relative difference between nonblinded and blinded trials. Among 467 randomized controlled trials included in 36 meta-analyses, 267 (57%) were considered blinded and 200 (43%) nonblinded. Intervention effect estimates were statistically significantly larger in nonblinded than blinded trials (combined ratio of odds ratio, 0.91; 95% CI, 0.84–0.99). We found no heterogeneity across meta-analyses ( p = 0.72; I 2 = 0%; τ 2 = 0). Sensitivity analyses adjusting the main analysis on risk of bias items yielded consistent results. CONCLUSIONS: Intervention effect estimates of mortality were slightly larger in nonblinded than blinded randomized controlled trials conducted in critical care, but confounding cannot be excluded. Blinding of both patients and personnel is important to consider when possible in critical care trials, even when evaluating mortality.